An integrated approach for assessing flood risk in Historic City Centres - Ferreira, Tiago M. (2020)
Historic city centres near watercourses are a specific type of urban area that are particularly vulnerable to flooding. In this study, we present a new methodology of flood risk assessment that crosses hazard and physical vulnerability information. We have selected the Historic City Centre of Guimarães (Portugal), a UNESCO Heritage Site, for developing and testing the defined methodology. The flood hazard scenario was obtained through the hydrologic–hydraulic modelling of peak flows with a 100-year return period, which provided flood extent, depths, and velocities. A decomposition of the momentum equation, using depth and velocity, allowed reaching a final hazard score. Flood vulnerability was assessed through combining an exposure component and a sensitivity component, from field-collected data regarding wall orientation, heritage status, age, number of storeys, condition, and material of buildings. By combining the results of the hazard and vulnerability modules in a risk-matrix, three qualitative levels of flood risk were defined. The individual and crossed analysis of results proved to be complementary. On one hand, it allows the identification of the more relevant risk factors—from the hazard or vulnerability modules. On the other hand, the risk-matrix identified other buildings with a high risk that otherwise would remain unnoticed to risk managers.